The synthesis of amphiphilic pillar[5]arene functionalized reduced graphene oxide and its application as novel fluorescence sensing platform for the determination of acetaminophen - Zhao, Genfu; Yang, Long; Wu, Shilian; Zhao, Hui; Tang, E; Li, Can-Peng (Biosensors & bioelectronics, 2017)
A sensitive and selective fluorescence approach based on a competitive host–guest interaction between amphiphilic pillar[5]arene (amPA5) and signal probe (acridine orange, AO)/target molecule (acetaminophen, AP) was developed by using amPA5 functionalized reduced graphene oxide (amPA5-RGO) as a receptor. Due to the host–guest interaction, AO and AP molecules both can enter into the hydrophobic inner cavity of amPA5 that could form a complex of 1:1 guest–host with amPA5 according to the size of molecules and the cavity of amPA5, but the AP interacts more strongly with amPA5 than with AO, so it can detect AP by the host-guest competition. The low detection limit of 0.05μM (S/N=3) and a linear response range of 0.1–4.0μM and 4.0–32μM for AP was obtained by using this method. It had lower detection limit and wider linear range than other methods, therefore, it was successfully utilized to detect AP in serum samples, and exhibited a promising application in practice. The molecular docking studies indicated that the major driving forces for the formation of the inclusion complex of AP and amPA5 are hydrogen bonding, π-π interactions, and hydrophobic interactions. Fluorescent approach for AP sensing using AO·amPA5-RGO as receptor. [Display omitted] •A novel fluorescent approach for acetaminophen sensing platform was constructed.•The determination of acetaminophen is based on a competitive host–guest interaction.•The method showed lower detection limit and wider linear range than other methods.•The interaction of competitive recognition was clarified by molecular docking study.